Bifurcation of magnetic island saturation controlled by plasma viscosity. (23rd March 2016) - Maget, P; Février, O; Lütjens, H; Luciani, J-F; Garbet, X
Abstract: Two nonlinear regimes, depending on the magnetic Prandtl number Prm, are identified for the magnetic islands described by resistive MHD equations. The frontier between these two regimes is sharp, and has the characteristics of a phase transition controlled by plasma viscosity. In the low Prm regime, a new form of the so-called flip instability, consisting of a sudden change in the island phase, is identified. Already known in the context of the forcing by external magnetic perturbations and localized current drive, it occurs spontaneously at low Prm. The main characteristics of this new structural instability are described. The low Prm regime is well described by the slab visco-resistive model in the linear phase, and is characterized by both a large saturation of the island and strong nonlinearly driven zonal flows (that do not significantly impact the island dynamics, however), while curvature physics strongly impacts the viscous regime.